Role of ChatGPT in the Essay Writing of Students: A Systematic Review of Literature - Madil, Wahyudin; Setyosari, Punaji; Kuswandi, Dedi; Ulfa, Saida (UIN Fatmawati Sukarno Bengkulu, 2024)
The growth and integration of Artificial Intelligence (AI) in the educational sector have been controversial. Recently, a new development called Chat Generative Pre-training Transformer (ChatGPT) has been gaining popularity, particularly among students. With this, many researchers are curious about the range of what it can do. Employing a systematic review of literature, this study aimed to identify the advantages and disadvantages of ChatGPT in the essay writing of students. Google Scholar was the main online database that was used. The screening and identification of articles utilized the inclusion-exclusion criteria and a PRISMA flowchart guide which yielded six (6) articles that were analyzed for the review. Through the Repertory Grid, the contrasts and similarities of the articles were identified. The findings of the study disclosed that one advantage of ChatGPT provides automated feedback. Further, the disadvantages of ChatGPT are the risk of plagiarism and the dependence and reliance of the students on the tool. While ChatGPT provides advantages and disadvantages in the essay writing of students, there are many considerations regarding the usage of this AI tool.